2011
DOI: 10.1186/1471-2180-11-18
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of membrane proteins of Mycobacterium tuberculosisH37Rv and H37Ra strains

Abstract: BackgroundThe potential causes for variation in virulence between distinct M. tuberculosis strains are still not fully known. However, differences in protein expression are probably an important factor. In this study we used a label-free quantitative proteomic approach to estimate differences in protein abundance between two closely related M. tuberculosis strains; the virulent H37Rv strain and its attenuated counterpart H37Ra.ResultsWe were able to identify more than 1700 proteins from both strains. As expect… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
64
2

Year Published

2011
2011
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 76 publications
(69 citation statements)
references
References 63 publications
3
64
2
Order By: Relevance
“…These results indicate that the classical model of outer membrane proteins as (predominantly) being ␤-barrels might not apply to all mycolate outer membrane proteins. Recently, various attempts were made to define proteins in the cell envelope or cell wall fractions of different strains of M. tuberculosis, M. bovis BCG, and Mycobacterium avium (20)(21)(22), but none were dedicated to the specific identification of MOMPs. In this study, we developed a method to specifically enrich for MOM proteins by differential detergent extraction of mycobacterial cell envelopes.…”
mentioning
confidence: 99%
“…These results indicate that the classical model of outer membrane proteins as (predominantly) being ␤-barrels might not apply to all mycolate outer membrane proteins. Recently, various attempts were made to define proteins in the cell envelope or cell wall fractions of different strains of M. tuberculosis, M. bovis BCG, and Mycobacterium avium (20)(21)(22), but none were dedicated to the specific identification of MOMPs. In this study, we developed a method to specifically enrich for MOM proteins by differential detergent extraction of mycobacterial cell envelopes.…”
mentioning
confidence: 99%
“…Malen et al [17] compared membrane proteins of M. tuberculosis H37Rv and H37Ra strains and examined the properties of more than 1700 proteins of both strains. Almost all identified proteins were too much similar, although strains were different in 5 or more proteins in 29 membrane or membrane associated proteins.…”
Section: Discussionmentioning
confidence: 99%
“…The results showed that 29 membrane-associated proteins with a 5 or more fold difference in their relative abundance in one strain compared to the other. Of which, 19 membrane-and lipo-proteins such as three ABC transporter proteins (Rv0933, Rv1273c and Rv1819c) had higher abundance in H37Rv, while another 10 proteins had a higher abundance in H37Ra [7]. Furthermore, Mehaffy et al [11] studied the proteomes of secreted and cytosolic proteins of genetically closely related strains of M. tuberculosis through 2DE and iTRAQ-LC-MS methods, and found that some enzymes such as GltA2, SucC, Gnd1 and Eno were expressed differently in different strains.…”
Section: Potential Biomarkers To Distinguish Different Strainsmentioning
confidence: 99%
“…During the last two years, a label-free proteomic method based on 1DE separation, LC-MS identification, followed by emPAI quantification was reported to identify differentially abundant proteins in closely related hypo-and hyper-virulent clinical Mycobacterium tuberculosis Beijing isolates [14]. Another label-free proteomics based on SDS-PAGE separation followed by MaxQuant peak intensity calculations was developed to analyze membrane proteins of Mycobacterium tuberculosis H37Rv and H37Ra strains [7].…”
Section: Quantitative Proteomic Studiesmentioning
confidence: 99%
See 1 more Smart Citation